2023
DOI: 10.1007/s42543-022-00057-x
|View full text |Cite
|
Sign up to set email alerts
|

Boundedness of Complements for Log Calabi–Yau Threefolds

Abstract: In this paper, we study the theory of complements, introduced by Shokurov, for Calabi–Yau type varieties with the coefficient set [0, 1]. We show that there exists a finite set of positive integers $$\mathcal {N}$$ N , such that if a threefold pair $$(X/Z\ni z,B)$$ ( X / Z ∋ z , B ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…This is considered to be much more difficult. See [10] for a similar result. Remark 6.3 (Explicit bound of threefold mlds).…”
Section: Further Remarksmentioning
confidence: 58%
“…This is considered to be much more difficult. See [10] for a similar result. Remark 6.3 (Explicit bound of threefold mlds).…”
Section: Further Remarksmentioning
confidence: 58%
“…According to the thermodynamic principle, during the solidification process of molten steel, the precipitation of carbides was accompanied by a decrease in its solubility, so the precipitation condition is that the actual solubility product of the elements generating carbides was greater than the equilibrium solubility product. [ 30,31 ] Therefore, the formation of carbides was judged by the calculation of solubility product and reaction Gibbs free energy change. The reaction formula of metal element M and carbon element C forming carbide M x C y in molten steel isx[ M ]+y[ C ]=MxCy$$x \left[\right.…”
Section: Resultsmentioning
confidence: 99%
“…It is also compelling to consider if explicit boundedness of N -complements can be established for varieties with more general coefficients. In fact, even for klt R-complementary pairs with arbitrary coefficients, it has been amazingly shown that the boundedness of complements still holds for Fano varieties [Sho20] (even for generalized pairs [CHHX23]), surfaces [CHX23] (see also [Zen23]), and threefolds [CHX23]. These results are expected to play a vital role in future birational geometry research.…”
Section: Proof Of the Main Theoremsmentioning
confidence: 98%
“…These results are expected to play a vital role in future birational geometry research. In particular, from the standpoint of explicit birational geometry, the results in [CHX23] led to question if explicit boundedness of N -complements for klt Rcomplementary threefolds with arbitrary, or at least DCC boundary coefficients, can be achieved. However, this appears to be a more challenging question, even in dimensions 2 and 3, and alternative approaches are required.…”
Section: Proof Of the Main Theoremsmentioning
confidence: 99%